2019
DOI: 10.1016/j.humpath.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

HuC/D expression in small round cell tumors and neuroendocrine tumors: a useful tool for distinguishing neuroblastoma from childhood small round cell tumors

Abstract: The RNA-binding protein HuC/D displays a neuron-specific expression and is involved in neuronal differentiation and the maintenance of the nervous system. Here we investigated the diagnostic value of HuC/D in neuroblastomas. We evaluated 85 neuroblastic tumors: 81 neuroblastomas; 3 ganglioneuroblastomas, intermixed; 1 ganglioneuroma, maturing; and 101 other tumors consisting of 34 Ewing sarcomas, 14 nephroblastomas, 11 rhabdomyosarcomas, 15 pulmonary small cell carcinomas, 18 pancreatic neuroendocrine tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Hierarchical clustering revealed that the genes could be readily categorized into 14 groups (Figure 5A). The study focused on the ELAVL3/HuC gene, which is an RNA-binding protein that displays a neuron-specific expression, 41,42 because the molecule was overexpressed by z50-fold in group XII. In addition, ALK overexpression is significantly associated with several general neuronal markers, including N-myc and Sox11, in uterine carcinosarcoma.…”
Section: Induction Of Elavl3/huc Expression Via Cooperation Of Alk An...mentioning
confidence: 99%
“…Hierarchical clustering revealed that the genes could be readily categorized into 14 groups (Figure 5A). The study focused on the ELAVL3/HuC gene, which is an RNA-binding protein that displays a neuron-specific expression, 41,42 because the molecule was overexpressed by z50-fold in group XII. In addition, ALK overexpression is significantly associated with several general neuronal markers, including N-myc and Sox11, in uterine carcinosarcoma.…”
Section: Induction Of Elavl3/huc Expression Via Cooperation Of Alk An...mentioning
confidence: 99%
“…ELAVL4 (HuD) had the most significant differential expression of its family (p = 1.6 × 10 −26 ). ELAVL2-4 are necessary and sufficient to induce neuronal differentiation [69], and are potential diagnostic markers of neuroblastoma (distinguishing neuroblastoma from similar tumours) [70]. They promote the stabilisation and/or translation of transcripts containing AU-rich elements (ARE), and Lazarova and colleagues found that ELAVL4 binds to the 3´UTR of the MYCN mRNA, stabilising it [71].…”
Section: Rbps Associated With Lower-risk Groupings and Involved In Nementioning
confidence: 99%
“…However, when it comes to neuroblastoma, an aggressive neural crest-derived tumor with an overall survival rate of less than 50%, several abnormal signal transduction pathways have been identified including: TP53, ALT, ADAM22, ATRX, GAL, RAS/MAPK, KLHL13, β3-adrenergic receptor, and TWIST1 (58,59). HuC/D, an RNA binding protein, may be a marker of neuroblastic cells but not a distinctive factor between neuroblastoma/ganglioneuroma (60). Tyrosine hydroxylase (TH) has been used as a sympathoadrenal marker for tumors originating from the neural crest, and currently Phox2B has been confirmed to be a better marker especially for undifferentiated neuroblastoma and cases with negative TH expression (61).…”
Section: Advanced Biomarkersmentioning
confidence: 99%